Iron deficiency and schooling attainment in Peru - Chong, Alberto; Cohen, Isabelle; Field, Erica; Nakasone, Eduardo; Torero, Máximo (American Economic Association, 2016)
Do nutritional deficiencies contribute to the intergenerational persistence of poverty by reducing the earnings potential of future generations? To address this question, we made available supplemental iron pills at a health center in rural Peru and encouraged adolescents to take them via media messages. School administrative data provide novel evidence that reducing iron deficiency results in a large and significant improvement in school performance and aspirations for anemic students. Our findings demonstrate that combining low-cost outreach efforts and local supplementation programs can be an affordable and effective method of reducing rates of adolescent iron deficiency anemia. (JEL I21, I23, I26, J24, J31, Q51, Q53)